Epithelial Ovarian Cancer: The Role of Cell Cycle Genes in the Different Histotypes - D’Andrilli, Giuseppina (Bentham Science Publishers Ltd., 2008)
Cancer is frequently considered to be a disease of the cell cycle; alterations in different families of cell cycle regulators cooperate in tumor development. Molecular analysis of human tumors has shown that cell cycle regulators are frequently mutated in human neoplasms, which underscores how important the maintenance of cell cycle commitment is in the prevention of human cancer. The regulatory pathways controlling cell cycle phases include several oncogenes and tumor suppressor genes which display a range of abnormalities with potential usefulness as markers of evolution or treatment response in epithelial ovarian cancer. This review summarizes the current knowledge about these aberrations in malignant tumors of the ovary. We sought to focus our attention on the genes involved in the development of tumors arising from the ovarian epithelium, which are the most common types of ovarian malignancies.